Social prescribing and students: A scoping review protocol. - Caitlin Muhl; Stephanie Wadge; Tarek Hussein (PLoS ONE)
Across the globe, student champions are building the social prescribing student movement. Given the numerous linkages between social prescribing and students, there is a need to understand the extent and type of evidence on social prescribing and students. Doing so will address an important gap in the literature, as there are no evidence reviews on this topic. Thus, this scoping review aims to understand the extent and type of evidence on social prescribing and students. This review will be conducted in accordance with the JBI methodology for scoping reviews and will be reported in line with the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). The search strategy will aim to locate both published and unpublished literature. No language or date restrictions will be placed on the search. The databases to be searched include MEDLINE (Ovid), CINAHL (EBSCO), Embase (Ovid), PsycINFO (Ovid), AMED (Ovid), ASSIA (ProQuest), Sociological Abstracts (ProQuest), Global Health (Ovid), Web of Science (Clarivate), Epistemonikos, JBI EBP Database (Ovid), and Cochrane Library. Sources of gray literature to be searched include Google, Google Scholar, Social Care Online (Social Care Institute for Excellence), SIREN Evidence and Resource Library (Social Interventions Research and Evaluation Network), and websites of social prescribing organizations and networks. Additionally, a request for evidence sources will be sent out to members of the Global Social Prescribing Student Council. Two independent reviewers will perform title and abstract screening, retrieval and assessment of full-text evidence sources, and data extraction. Data analysis will consist of basic descriptive analysis. Results will be presented in tabular and/or diagrammatic format alongside a narrative summary.